The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.7150/ijbs.8.1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antitumor Efficacy of Gemcitabine by Evodiamine on Pancreatic Cancer via Regulating PI3K/Akt Pathway

Abstract: Evodiamine has therapeutic potential against cancers. This study was designed to investigate whether combination therapy with gemcitabine and evodiamine enhanced antitumor efficacy in pancreatic cancer. In vitro application of the combination therapy triggered significantly higher frequency of pancreatic cancer cells apoptosis, inhibited the activities of PI3K, Akt, PKA, mTOR and PTEN, and decreased the activation of NF-κB and expression of NF-κB-regulated products. In vivo application of the combination thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 46 publications
5
48
0
Order By: Relevance
“…The extract was dried on anhydrous Na 2 SO 4 , the EtOAc was removed and the crude product was purified by column chromatography to afford the pure target compounds. The characterization data for these compounds was as follows: (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Yellowish product 1.22 g, yield 53.8%, m.p.…”
Section: Synthesis Of N13-substituted Evodiamine Derivatives: Generalmentioning
confidence: 99%
See 2 more Smart Citations
“…The extract was dried on anhydrous Na 2 SO 4 , the EtOAc was removed and the crude product was purified by column chromatography to afford the pure target compounds. The characterization data for these compounds was as follows: (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Yellowish product 1.22 g, yield 53.8%, m.p.…”
Section: Synthesis Of N13-substituted Evodiamine Derivatives: Generalmentioning
confidence: 99%
“…(5 (6). This compound was obtained by the hydrolysis of 9-(2,2-diethoxyethyl)evodiamine (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Into a solution of 2-18 (1.26 g, 3.0 mmol) in ethanol (20 mL) was added 10% hydrochloric acid (10 mL), and the mixture was stirred for 4-5 h at room temperature, while monitored by TLC.…”
Section: Synthetic Procedures For 3-1-3-3mentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al 40 reported that the IC 50 of GEM after a 48-h exposure is 16 μg/mL, and Celano et al 41 observed a significant effect at 100 μM GEM after a 72-h treatment. Cell viability in SW1990 cells, treated with 20 μM GEM, was reduced to 57% after 24 h. 42 Zhang et al 43 demonstrated that GEM induced a dose-and time-dependent decrease in the proliferation of the lung cancer cell line SPC-A-1. Compared with that of the control cells, SPC-A-1 cells showed a 60%, 35%, and 18% reduction in the levels …”
Section: Effect Of Agnps and Gem On Cell Viabilitymentioning
confidence: 99%
“…All animal studies were approved by the Animal Research and Ethical Committee of Wenzhou Medical College (Zhejiang, China). Pancreatic cancer xenograft tumor model was performed as described in our previous studies (25,26). PANC-1 cells (5x10 6 ) in 200 µl complete culture medium were injected subcutaneously into the right flank of each mouse.…”
Section: Real-time Polymerase Cahin Reaction (Pcr)mentioning
confidence: 99%